2003
DOI: 10.1128/jb.185.10.3167-3178.2003
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Generating Enzymes ofBurkholderia cepaciaand Their Interactions with Macrophages

Abstract: We previously demonstrated that several clinical and environmental isolates of Burkholderia cepacia secreted ATP-utilizing enzymes to the medium; the secretion of these enzymes by cystic fibrosis lung isolate strain 38 was shown to be greatly enhanced in the presence of ␣ 2 -macroglobulin. Fractionation of the growth medium of cystic fibrosis isolate strain 71 belonging to genomovar I demonstrated the presence of two additional proteins, homologues of Pseudomonas aeruginosa azurin and cytochrome c 551 , which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Moreover, after intensive studies, the group of Das Gupta patented some azurin fragments with low toxicity for their use in cancer prevention. However, in contrast to this group, Puni et al, 102 found that azurin can induce apoptosis in macrophages in a caspase‐dependent manner. Very recently Sasidharan et al 103 proposed to use azurin and its fragment p28, as anti‐SARS‐CoV‐2 inhibitor.…”
Section: Acidic Sequencesmentioning
confidence: 81%
“…Moreover, after intensive studies, the group of Das Gupta patented some azurin fragments with low toxicity for their use in cancer prevention. However, in contrast to this group, Puni et al, 102 found that azurin can induce apoptosis in macrophages in a caspase‐dependent manner. Very recently Sasidharan et al 103 proposed to use azurin and its fragment p28, as anti‐SARS‐CoV‐2 inhibitor.…”
Section: Acidic Sequencesmentioning
confidence: 81%
“…Both apoptotic and necrotic cell death have been described in murine macrophages and human neutrophils following exposure to purified secreted BCC enzymes such as hemolysin, ATP-utilizing enzymes, azurin and cytochrome c551 (Hutchison et al, 1998;Melnikov et al, 2000;Punj et al, 2003). In rodent models, extracellular proteases are associated with tissue damage, and the production of at least one zinc metalloprotease is required for virulence (McKevitt et al, 1989;Kooi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In rodent models, extracellular proteases are associated with tissue damage, and the production of at least one zinc metalloprotease is required for virulence (McKevitt et al ., 1989; Kooi et al ., 2006). Of particular interest, azurin and ZmpB are secreted by B. cenocepacia but not by B. multivorans (Punj et al ., 2003; Kooi et al ., 2006) . The relevance of those studies to the present one is unclear because, in our investigations, DCs remained viable when exposed to BCC supernatants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that subinhibitory concentrations of CAZ modulate the biogenesis of OMVs and stimulate the association of cytotoxic factors with B. cepacia OMVs. Azurin homologue in the culture supernatant of B. cepacia and hemolysin from B. cepacia genomovar III were found to be cytotoxic to host cells [49,50]. However, the present study did not determine the cytotoxic factors of B. cepacia OMVs and it is necessary to clarify cytotoxic factors packaged in B. cepacia OMVs and their association with host cell death.…”
Section: Discussionmentioning
confidence: 67%